Liposomal Vesicles : Obtention, Properties and Potential Applications in Biomedicine - Lanio, M. E.; Luzardo, M. C.; Laborde, R.; Sánchez, O.; Cruz-Leal, Y.; Pazos, F.; Tejuca, M.; Valle, A.; Alonso, M. E.; Fernández, L. E.; Álvarez, C. (Revista Cubana de Física; Vol 26 No 1 (2009): Cuban Nanotechnology 2009, 2009)
Liposomes have been used as membranes models and carriers of enormous diversity of molecules with biochemical, nanobiotechnological and biomedical purposes. Considering the versatility in physico-chemical properties of these vesicles, they are attractive to design vehicles for proteins, DNA, drugs, etc. In this work, we summarize the liposomal technologies and the procedures most frequently used to study the physico-chemical characteristics of these vesicles, such as size, structural features, physical and chemical stability, electric properties and phase transitions. Liposomes are employed as immunoadjuvants due to their ability to address antigens to cells of the immune system. Additionally, the present paper describes results obtained by our group in the study of the immunmodulating properties of liposomal lipids for antigens such as EGFhr, among others.